2002
DOI: 10.1103/physrevd.65.093017
|View full text |Cite
|
Sign up to set email alerts
|

Seesaw tau lepton mass and calculable neutrino masses in a 3-3-1 model

Abstract: In this work we show that in a version of the 3-3-1 model proposed by Duong and Ma, in which the introduction of a scalar sextet is avoided by adding a singlet heavy charged lepton, the lepton gains mass through a seesawlike mechanism. We also show how to generate neutrino masses at the one-loop level, and give the respective Maki-Nakagawa-Sakata mixing matrices for a set of the parameters. We also consider the effect of adding a singlet right-handed neutrino. DOI: 10.1103/PhysRevD.65.093017 PACS number͑s͒: 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Models for neutrino masses generation in the 3-3-1 model are discussed in several papers [13,14]. We show that our scheme can be compatible with the one of the Ref.…”
Section: Neutrino Massessupporting
confidence: 61%
“…Models for neutrino masses generation in the 3-3-1 model are discussed in several papers [13,14]. We show that our scheme can be compatible with the one of the Ref.…”
Section: Neutrino Massessupporting
confidence: 61%
“…There are two simple possibilities to generate a realistic charged lepton spectrum. One of them is to introduce a vector-like pair of singlet charged fermions [48,49]. We will call this version of the model PPF-E.…”
Section: Models Based On the 331 Groupmentioning
confidence: 99%
“…7 That the wrong prediction for the charged lepton spectrum in the PPF model can be cured using vector-like leptons was noted already in [69,70].…”
Section: Extended Ppf Modelsmentioning
confidence: 99%
“…We have found that several of the originally proposed 331 models can not explain correctly the observed neutrino masses (nor charged lepton masses, in one case). Thus, it is necessary to extend these models and we present several possible modifications that can bring these models in agreement with experimental data, some of which have already been considered before [14,[66][67][68][69][70]. We focus here (mostly) on neutrino masses and mixings and leave aside other LNV processes, which we mention only briefly when it is relevant.…”
Section: Introductionmentioning
confidence: 99%